Improving the Stability of Mining Slopes in Tarcha Coal Mine, Southwestern Ethiopian Deposit Through Geometric Adjustments - Getaneh Abebay; Endalu Tadele Chala; Nagessa Zerihun Jilo; Tiyasha Tiyasha (Advances in Civil Engineering)
The Tarcha coal deposit, located beneath the Omo trachyte flows in the Omo-Gibe River basin of southern Ethiopia, is actively mined using open-pit methods for energy resources. However, these mines face significant slope instability issues. This study aims to assess and enhance the stability of the selected open-pit coal mine quarries through field and laboratory analyses, supported by the limit equilibrium method (LEM) and the finite element method (FEM). Fieldwork involved detailed measurements of slope geometry and orientation, in situ rock testing, and soil and rock sampling for laboratory analysis. Results indicated that the rock quality designation (RQD) of the rocks ranged from 22 to 57.5, indicating rock quality from very poor to fair. Schmidt hammer tests revealed uniaxial compressive strength (UCS) values between 14.79 and 29.31 MPa. Soil analysis classified the soils as sand with low to high plasticity (8.89% to 31.86%) and a liquid limit range of 21% to 62.63%. Stability analyses using LEM and FEM on two critical slopes (MS-1 and MS-2) under saturated, unloading, and loading conditions indicated instability. However, geometric adjustments, such as reducing slope angle, decreasing slope height, and implementing benching, were found to significantly improve slope stability.